Stuart Hall - Procter, James (Routledge critical thinkers., 2004)
Stuart Hall is the ideal gateway to the work of a critic described by Terry Eagleton as 'a walking chronicle of everything from the New Left to New Times, Leavis to Lyotard, Aldermaston to ethnicity'